DYNAMICS OF PROTEINS OF THE ACUTE PHASE OF INFLAMMATION IN PARATONSILLAR ABSCESSES IN RESIDENTS OF THE INDUSTRIAL CITY - Осипов, Виктор Дмитриевич; Павлов, Вениамин Витальевич; Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Мотуз, Ирэна Юрьевна; Пестерева, Дина Викторовна; Штайгер, Варвара Адамовна (Medicine in Kuzbass, 2022)
Significant experience has been accumulated in the study and treatment of chronic tonsillitis, but the incidence of this pathology is not decreasing.Subject – 60 residents of Novokuznetsk aged 19 to 40 with upper paratonsillar abscess were examined.Objective – study of changes in the content of proteins of the acute phase of inflammation (interleukin-6, procalcitonin, presepsin and C-reactive protein) in patients with paratonsillar abscesses, before and after abscess drainage.Methods. The microflora of the contents was studied at the opening of a paratonsillar abscess in 50 patients. Proteins of procalcitonin, presepsin, C-reactive protein and interleukin-6 were determined before the opening of the paratonsillar abscess and one to two days after the opening. Procalcitonin and presepsin were determined by the quantitative method of immunoenzymatic chemiluminescence. C-reactive protein – immunoturodimetric method. The content of interleukin-6 in the blood serum was studied by the enzyme-linked immunosorbent assay using the test systems of the Vector-Best company. Statistical processing of the obtained data was carried out using the software packages «MS-EXCEL», «BIOSTAT».Main results. ß-, γ-hemolytic streptococcus was found in 30 patients. Streptococcus viridans was inoculated in 10 cases, gram-negative Klebsiella flora in combination with Candida albicans and aerobic bacillus in 10 patients. A statistically significant increase in the content of interleukin-6, presepsin and C-reactive protein was revealed before drainage of paratonsillar abscesses. The levels of presepsin and C-reactive protein 24-48 hours after the opening of paratonsillar abscesses remain statistically significantly high, and the content of interleukin-6 comes to normal values.Conclusions. This study of the dynamics of proteins in the acute phase of inflammation is preliminary and requires further research, but it will be useful in the treatment of patients with peritonsillar abscesses and predicting the outcome of the disease.
Keywords: paratonsillar abscess; acute phase proteins; interleukin-6; procalcitonin; presepsin; C-reactive protein